Stereotactic Radiosurgery for Benign (World Health Organization Grade I) Cavernous Sinus Meningiomas—International Stereotactic Radiosurgery Society (ISRS) Practice Guideline: A Systematic Review. Issue 6 (15th March 2018) - Lee, Cheng-Chia; Trifiletti, Daniel M; Sahgal, Arjun; DeSalles, Antonio; Fariselli, Laura; Hayashi, Motohiro; Levivier, Marc; Ma, Lijun; Álvarez, Roberto Martínez; Paddick, Ian; Regis, Jean; Ryu, Samuel; et al.
Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) has become popular as a standard treatment for cavernous sinus (CS) meningiomas. OBJECTIVE: To summarize the published literature specific to the treatment of CS meningioma with SRS found through a systematic review, and to create recommendations on behalf of the International Stereotactic Radiosurgery Society. METHODS: Articles published from January 1963 to December 2014 were systemically reviewed. Three electronic databases, PubMed, EMBASE, and The Cochrane Central Register of Controlled Trials, were searched. Publications in English with at least 10 patients (each arm) were included. RESULTS: Of 569 screened abstracts, a total of 49 full-text articles were included in the analysis. All studies were retrospective. Most of the reports had favorable outcomes with 5-yr progression-free survival (PFS) rates ranging from 86% to 99%, and 10-yr PFS rates ranging from 69% to 97%. The post-SRS neurological preservation rate ranged from 80% to 100%. Resection can be considered for the treatment of larger (>3 cm in diameter) and symptomatic CS meningioma in patients both receptive to and medically eligible for open surgery. Adjuvant or salvage SRS for residual or recurrent tumor can be utilized depending on factors such as tumor volume and proximity to adjacent critical organs at risk. CONCLUSION: The literature is limited to level III evidence with respect to outcomes of SRS in patients with CS meningioma. Based on the observed results, SRS offers a favorable benefit to risk profile for patients with CS meningioma.